The Factors that Influence the Performance of Daily Workers: Individual Character, Ability, and Motivation: (A Case Study of Human Resource Management in PT GMIT Jember) - Sefri Ton; Aida Vitayala Hubeis; Tanti Kustiari (Sultan Publisher, 2023)
Tobacco management by companies is quite popular, especially in Jember Regency. Tobacco will be produced in warehouses before being sold to cigarette companies. The company's problem is the quality factor of human resources, especially daily workers in the warehouse. Daily workers working in warehouses have different individual characteristics and abilities. In addition, daily workers have varied work motives and can have an impact on company performance. The research objective was to analyse the effect of individual character, ability, and work motivation on the performance of daily warehouse workers. This research uses a quantitative descriptive approach with a survey method. The research sample consisted of 105 respondents from a total population of 215 daily workers warehouse. The sampling technique in this study was carried out systematically (systematic sampling). Descriptive analysis is based on the average (mean) value of each indicator, and then interpretation of the respondents' answers is carried out using the three-box method criteria. Testing the hypothesis using Structural Equation Model analysis, and MS Excel 2010. The results showed that individual character and ability had a significant effect on performance. Meanwhile, work motivation has no significant effect on performance.